Principal Performance and Leadership in Facing Covid-19 Pandemic at SMK Muhammadiyah 1 Surakarta - Agus Maryanto (Walidem Institute and Publishing (WIP), 2023)
The Objectives of this research are; 1) Analyze the performance of the principal at SMK Muhammadiyah 1 Surakarta in facing the crisis period due to Covid-19; 2) Analyse the leadership of the principal of SMK Muhammadiyah 1 Surakarta in facing the crisis due to the Covid-19 pandemic; 3) Analyze the principal's strategy at SMK Muhammadiyah 1 Surakarta in facing the crisis due to the Covid-19 pandemic. This type of research is descriptive qualitative research. The subject of this research is the Head of SMK Muhammadiyah 1 Surakarta. Data was collected from observations, and interviews. The research results show; 1) The performance of the Head of SMK Muhammadiyah 1 Surakarta in facing the Covid-19 pandemic is shown as an educator, manager, administrator, supervisor, innovator and motivator; 2) The leadership of the Head of SMK Muhammadiyah 1 Surakarta in facing the Covid-19 pandemic is proven by carrying out activities that demonstrate his ability to make decisions, take responsibility, communicate, coordinate subordinates, and control emotions.